Integrating Pancasila Values into Civic Education Curriculum through Technology to Strengthen National Identity and Unity - Laros Tuhuteru; Danan Wuryanto Pramono (JTP - Jurnal Teknologi Pendidikan, 2025)
This study examines the integration of Pancasila values into the civic education curriculum using technology as a means to strengthen national identity and unity. As technological advancements continue to shape educational practices, the study addresses the gap in effectively teaching Pancasila, a crucial aspect of Indonesia's national philosophy. Through a library research methodology, the study reviews relevant literature, including books, academic journals, and previous studies. The findings indicate that traditional teaching methods have struggled to deeply instill Pancasila values, often failing to engage students meaningfully. However, technology presents a promising opportunity to enhance students' understanding and engagement with these values, providing interactive and innovative platforms for learning. This research contributes to the theoretical development of civic education and offers practical recommendations for incorporating technology into the curriculum to promote national identity and unity. The study emphasizes the potential of digital tools to create more dynamic and inclusive learning experiences. However, its reliance on secondary data poses limitations, highlighting the need for future empirical research to validate and expand upon the findings.